Retrospective Analysis of Allergen Distribution Dynamics in Central Taiwan - Tseng, Yu-Wei; Er, Tze-Kiong (British Journal of Biomedical Science, 2023)
Introduction: Allergy is a type Ⅰ hypersensitivity reaction to certain substances (allergens) such as environmental factors, food and drugs. Allergies are a significant public health issue, and therefore, understanding the distribution patterns of allergens in specific regions is important. This study aimed to retrospectively analyse allergen distribution patterns in Central Taiwan over a 5 years period (2018–2022). Methods: Data of patients who had allergen sensitization testing using the OPTIGEN® Allergen-Specific IgE Assay from the 1st of January 2018 to the 31st of December 2022 were reviewed retrospectively. Statistical analyses were performed to determine the prevalence and distribution of allergens in our study population. Results: A total of 8,444 patients (3,784 males and 4,660 females) who attended the Asia University Hospital for allergen detection were enrolled in this study. Dermatophagoides farina (41.8%), Dermatophagoides pteronyssinus (37.9%), house dust (24.6%), cockroach mix (17.7%), crab (12.6%), clam (9.8%), shrimp (9.1%), cat dander (8.1%), pig weed (8%) and peanut (7.8%) were identified as the ten allergens that most commonly induced sensitization in our study population. Additionally, crab, clam, shrimp, peanut and beef were the five most common food allergens. Conclusion: In summary, our findings contribute significantly to the knowledge on allergen distribution in Central Taiwan. Our identification of prevalent allergens may contribute to an improved understanding of the epidemiology of allergies in this region.